FRANSUZ TILI DARSLARIDA O'YINLARDAN FOYDALANISH («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the success rate of using games in foreignlanguage learning.
Keywords: linguistic games, small groups, sunflower game, blackboard, let's play together, idea.